2011
DOI: 10.1111/j.1601-183x.2011.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Val66Met and cognition: all, none, or some? A meta‐analysis of the genetic association

Abstract: The Val66Met, G196A (rs6265) polymorphism in the brain-derived neurotrophic factor gene, BDNF, located at 11p13, has been associated with a wide range of cognitive functions. Yet, the pattern of results is complex and conflicting. In the current study we conducted a meta-analysis that included 23 publications containing 31 independent samples comprised of 7,095 individuals. The phenotypes that were examined in this analysis covered a wide variety of cognitive functions and included indicators of general cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 63 publications
4
96
0
1
Order By: Relevance
“…9 However, recent meta-analyses investigating the relationship between the functional BDNF Val66Met polymorphism and performance on memory tasks have suggested heterogeneity in odds ratios among subjects. 3,10 For example, some genetic association studies found impaired episodic memory performance in BDNF Met allele carriers compared to Val/Val homozygotes, [11][12][13] whereas other reports found no effect of the BDNF Val66Met polymorphism on memory.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, recent meta-analyses investigating the relationship between the functional BDNF Val66Met polymorphism and performance on memory tasks have suggested heterogeneity in odds ratios among subjects. 3,10 For example, some genetic association studies found impaired episodic memory performance in BDNF Met allele carriers compared to Val/Val homozygotes, [11][12][13] whereas other reports found no effect of the BDNF Val66Met polymorphism on memory.…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations for future research include replication in larger samples of mixed race participants in which population stratification is corrected for and in which the Met66Met genotype is better represented (Notaras et al, 2015). Furthermore, variation across the BDNF gene would be useful to consider (Mandelman & Grigorenko, 2012). Additionally, the effect of other genetic variants, in conjunction with the BDNF Val66Met polymorphism, should be explored given findings of an epistatic effect between BDNF and the serotonin transporter genes (Martinowich & Lu, 2008; Pezawas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have investigated the effect of BDNF val66met on cognition and the results are mixed. A recent meta-analysis could not establish any significant influence of BDNF val66met on general cognitive ability, memory, executive function, visual processing skills, or cognitive fluency (Mandelman & Grigorenko, 2012). However, this meta-analysis did not permit an analysis of age stratifying effects on the association between the BDNF val66met and cognition.…”
Section: Bdnf and Odor Identificationmentioning
confidence: 96%
“…Hence, the overall pattern of findings regarding the BDNF val66met as a candidate gene for cognition presents a complex and conflicting pattern of results. A recent meta-analysis did not establish significant associations for the genotype and any of the included phenotypes, such as general cognitive ability, memory, executive functions, visual processing skills or verbal fluency (Mandelman & Grigorenko, 2012). However, this meta-analysis did not take age or sex into account to stratify for any effects on the association between the BDNF val66met polymorphism and cognition.…”
Section: Bdnf and Cognitionmentioning
confidence: 99%